Psychological And Pedagogical Support For Working Full-time Students - Tkachenko S. V. (Pedagogy, Psychology, Society: from theory to practice, 2025)
The article examines the issue of students combining work and study, presents the results of a survey of students about the motives for their decision to earn money, and offers psychological and pedagogical recommendations for helping students
Keywords: вуз; студент; образовательная организация; стресс; educational organization; university; психолого-педагогическая поддержка; stress; student; psychological and pedagogical support; работа; учёба; work; study